A proof-of-concept point-of-care test for the serodiagnosis of human amebic liver abscess - Rutchanee Rodpai; Penchom Janwan; Lakkhana Sadaow; Patcharaporn Boonroumkaew; Oranuch Sanpool; Tongjit Thanchomnang; Hiroshi Yamasaki; Toshihiro Mita; Pewpan M. Intapan; Wanchai Maleewong (PeerJ)
Background Amebic liver abscess (ALA), caused by an extraintestinal invasion of the virulent protozoan Entamoeba histolytica, is important among parasitic causes of morbidity and mortality, especially in the tropics. Clinical symptoms, medical-imaging abnormalities of the liver and serological tests are normally made for supportive diagnosis. Serum-based enzyme-linked immunosorbent assay (ELISA) has been conventionally used for diagnosing ALA but is time-consuming and sophisticated equipment is required. Therefore, we sought to develop a new and rapid innovative point-of-care immunochromatographic test (ICT) that can use whole blood as an alternative to serum-based ELISA. An ICT tool using simulated whole-blood samples was developed for immunoglobulin G antibody detection, and its diagnostic efficiency was evaluated in comparison with serum-based ELISA. Methods Both methods were tested to assess their diagnostic performance using a total of 253 serum samples. These came from ALA patients (n = 13), healthy individuals (n = 40), and patients with other diseases (n = 200). Results Amebiasis-ICT exhibited 100% (95% confidential interval (CI) [75.3–100.0]) sensitivity and 97.1% (95% CI [94.1–98.8]) specificity, whereas ELISA gave the same sensitivity (100% 95% CI [75.3 –100.0]) and slightly lower specificity (95.8% 95% CI [92.5–98.0]). There were no significant differences in sensitivity and specificity between the two tests (Exact McNemar’s test; p > 0.05), with Cohen’s kappa agreement 96.44% (κ-value = 0.771, p < 0.001) indicating substantial agreement. Conclusion This ICT tool using simulated whole-blood samples has a high possibility of being used with real whole blood. Therefore, since there is no need to separate serum, this can be considered an innovative diagnostic tool to replace serum-based ELISA in clinics and field surveys in remote areas where medical facilities are limited.